Entropy Generation in C6H9NAO7 Fluid Over an Accelerated Heated Plate - Ahmed, Tarek Nabil; Khan, Ilyas (Frontiers in Physics, 2020)
In this article, C6H9NaO7 fluid is considered over an accelerated vertical plate. The plate is heated from the bottom. Non-Newtonian model of C6H9NaO7 (Sodium Alginate) is considered. Convection term in momentum equations is also taken. The dimensionless form of the problem is constructed based on the dimensionless variables. The integral transformation of Laplace is used for developing the exact solution to the problem. Explicit expressions are obtained the field of velocity and distribution of temperature. Based on that, the skin-friction and Nusselt number results for corresponding are computed. Equations for entropy generation (EG) and Bejan number (BN) are developed. Results are plotted and discussed for embedded parameters. Most significantly, the results for EG and BN are computed and discussed.